The relationship between fear of missing out and mobile phone addiction among college students: the mediating role of depression and the moderating role of loneliness - Liu, Nana; Zhu, Siyu; Zhang, Weixin; Sun, Yanyan; Zhang, Xinyao (Frontiers in Public Health, 2024)
Background Mobile phone addiction has adverse influences on the physical and mental health of college students. However, few studies shed light on the effect of fear of missing out on mobile phone addiction and the underlying mechanisms among college students. Methods To explore their associations, the present study used the Fear of Missing Out Scales (FoMOS), Loneliness Scale (USL-8), Mobile Phone Addiction Index Scale (MPAI), and Depression-Anxiety-Stress Questionnaire (DASS-21) to investigate 750 college students. Results The results suggested that fear of missing out significantly positively predicted mobile phone addiction. This direct effect could be mediated by depression, and the indirect effect of fear of missing out on mobile phone addiction could be moderated by loneliness. Specifically, the indirect effect was stronger for students with high levels of loneliness. Conclusion This study provides a theoretical basis for developing future interventions for mobile phone addiction in higher education students.